1973
DOI: 10.1243/jmes_jour_1973_015_031_02
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Modes and Frequencies of Beams Translating between Fixed end Supports

Abstract: The effects of longitudinal steady translational motion on the vibration frequencies and modes of simple Euler beams are outlined. An example shows that the natural frequencies decrease monotonically with increasing translation velocity, while the mode shapes are complex, indicating significant phase disparities from point to point across the span. Divergence is shown to occur when the translation velocity is greater than the fundamental flexural wave propagation velocity. More general equations of motion, go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 4 publications
0
32
0
Order By: Relevance
“…See e.g. Archibald and Emslie (1958), Miranker (1960), Swope and Ames (1963), Simpson (1973), Chonan (1986), Wickert and Mote (1990), Shen et al (1995), Wang (2003), Shin et al (2005), Sygulski (2007), and Kulachenko et al (2007a,b).…”
Section: Introductionmentioning
confidence: 99%
“…See e.g. Archibald and Emslie (1958), Miranker (1960), Swope and Ames (1963), Simpson (1973), Chonan (1986), Wickert and Mote (1990), Shen et al (1995), Wang (2003), Shin et al (2005), Sygulski (2007), and Kulachenko et al (2007a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Mote [1] studied the band saw vibrations by regarding it as an axially moving beam and the frequency curves were obtained. Simpson [2] analyzed the natural frequencies and mode curves of the axially moving beam with clamped boundary, his calculated results show that modes distorted violently as the moving speed increases. Moreover, Wickert [3] brought forth that axially moving beam belongs to gyroscopic system and researched the forced vibration of axially moving beam by modal analysis and Green's function method.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of axial motion of the material on its frequency spectrum and eigenfunctions were investigated for strings by (2) and for beams by (33). It was shown that the natural frequency of each mode decreases when the transport speed increases, and that the travelling string and beam both experience divergence instability at a sufficiently high speed.…”
Section: Introductionmentioning
confidence: 99%